Pengaruh Dewan Direksi, Komite Audit, dan Kepemilikan Asing Terhadap Kinerja Keuangan - Afifah, Ulfa; Gustriani, Bunga Yefita; Surya, Raja Adri Satriawan; Zarefar, Atika; Zarefar, Arumega; Khoiriyah, Mayla; Ramaiyanti, Sinta (Akuntansi & Ekonomika, 2024)
This study aims to determine the effect of the board of directors, audit committee and foreign ownership on financial performance in consumer cyclicals sector companies listed on the IDX in 2014-2022. The sampling technique used purposive sampling and obtained 37 companies. This study uses quantitative data and the research method uses regression analysis using the STATA application. The results of this study indicate that the board of directors and audit committee have a positive effect on financial performance, but foreign ownership with a level of 21% has a negative effect on financial performance. The results of this study are practically useful for knowing the more in-depth functions of the independent board of directors, independent audit committee, and foreign ownership and utilizing these variables to improve the company's financial performance.